Improving thermoelectric properties of p-type (BiSb)2(TeSe)3 single crystal by Zr doping - Požega Emina; Vuković Nikola; Gomidželović Lidija; Janošević Miloš; Jovanović Milenko; Marjanović Saša; Mitrović Milijana (Science of Sintering, 2023)
In order to study the effect of Zr doping on the thermoelectric properties of p-type Bi10.17Sb30.72 Zr0.35Te58.28Se0.48 single crystal, аn ingot was prepared by Bridgman method. Cut and cleaved samples from different regions of ingot were characterized by a Hall Effect based on the Van der Pauw method. The first measurements were conducted with four ohmic contacts at room temperature and the obtained results were presented in our investigation, earlier. Аlso, high charge carriers mobility was obtained on the sample with silver contacts at the temperature of liquid nitrogen. Single crystal was characterized by Seebeck coefficient (S), conductivity (κ) and resistivity (ρ) measurements as а function of temperature in the range of 40-320°C by a home-made impedance meter. The prepared single crystal has a figure of merit (Z) of 1.22 x 10-3 K-1 at 300°C.